AI-based Autonomous Weapons and Individual Criminal Responsibility under the Rome Statute - Fareed Mohd Hassan; Noor Dzuhaidah Osman (Kazan Innovative University named after V.G. Timiryasov, 2024)
Objective: international law obligates states to prosecute those who have violated laws in armed conflicts, particularly when the international community now has International Criminal Court (ICC).